| $\displaystyle x+1$ | $\displaystyle x$ | $\displaystyle x-1$ | $\displaystyle x-2$ | $\displaystyle (x+1)x(x-1)(x-2)$ | $\displaystyle (x+1)x(x-1)(x-2)\le 0$ |

$\displaystyle x=-2$ | -1 | -2 | -3 | -4 | 24 | FALSE |

$\displaystyle x=-1$ | 0 | -1 | -2 | -3 | 0 | TRUE |

$\displaystyle x=-\tfrac{1}{2}$ | $\displaystyle \tfrac{1}{2}$ | $\displaystyle -\tfrac{1}{2}$ | $\displaystyle -\tfrac{3}{2}$ | $\displaystyle -\tfrac{5}{2}$ | $\displaystyle -\tfrac{15}{8}$ | TRUE |

$\displaystyle x=0$ | 1 | 0 | -1 | -2 | 0 | TRUE |

$\displaystyle x=\tfrac{1}{2}$ | $\displaystyle \tfrac{3}{2}$ | $\displaystyle \tfrac{1}{2}$ | $\displaystyle -\tfrac{1}{2}$ | $\displaystyle -\tfrac{3}{2}$ | $\displaystyle \tfrac{9}{8}$ | FALSE |

$\displaystyle x=1$ | 2 | 1 | 0 | -1 | 0 | TRUE |

$\displaystyle x=\tfrac{3}{2}$ | $\displaystyle \tfrac{5}{2}$ | $\displaystyle \tfrac{3}{2}$ | $\displaystyle \tfrac{1}{2}$ | $\displaystyle -\tfrac{1}{2}$ | $\displaystyle -\tfrac{15}{8}$ | TRUE |

$\displaystyle x=2$ | 3 | 2 | 1 | 0 | 0 | TRUE |

$\displaystyle x=3$ | 4 | 3 | 2 | 1 | 24 | FALSE |